Error of disclosure - N. Strobbe (Law Text Culture, 1998)
Was it that there was no law, no land, a land of no one, nothing (terra nullius)? A land, but a land without anyone or anything (a land of nobody's, no one, a land that belonged to the nothing of this other one who by force and contract will have been turned into the subject of this law) or, more precisely, a land with nothing, a land of nothing, a land with a very particular nothing. This land whose non-law, ostensibly, will have become, at once for the future and throughout its indeterminate past (but how could these be separated for a land which was said to have lacked what an officer of the English state could not discover?), a land whose nonsite would be erased in the name of a sovereign law that recognisedjus nullius in the site of law's dominion, demanding in this relation that law enact itself in the very site of its absence (where this nothing would be returned to the identity ofa law that recognised nothing but its law of identity).